2012
DOI: 10.1007/s10815-011-9704-8
|View full text |Cite
|
Sign up to set email alerts
|

Empty follicle syndrome after GnRHa triggering versus hCG triggering in COS

Abstract: Purpose This study aimed to explore the incidence of empty follicle syndrome (EFS) in oocyte donors who had final oocyte maturation triggered with GnRHa and to compare the incidence of EFS in this group of patients with IVF patients who had final oocyte maturation with hCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 30 publications
2
74
0
4
Order By: Relevance
“…The incidence of EFS has been reported as 0.6%-3.5% in GnRHa trigger cycles, which is similar to that reported (0.1%-3.1%) after an hCG trigger (12,19,(25)(26)(27)(28)(29). Therefore, EFS is not an inherent and exclusive problem to the GnRHa trigger (25) but could be related to human error, abnormalities in the in vivo biological activity of some batches of commercially available GnRHa, hypothalamic dysfunction, or GnRH receptor mutations (23,26,(28)(29)(30). Elucidating the relationship between lower doses of GnRHa and EFS will require further studies including a larger number of patients.…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of EFS has been reported as 0.6%-3.5% in GnRHa trigger cycles, which is similar to that reported (0.1%-3.1%) after an hCG trigger (12,19,(25)(26)(27)(28)(29). Therefore, EFS is not an inherent and exclusive problem to the GnRHa trigger (25) but could be related to human error, abnormalities in the in vivo biological activity of some batches of commercially available GnRHa, hypothalamic dysfunction, or GnRH receptor mutations (23,26,(28)(29)(30). Elucidating the relationship between lower doses of GnRHa and EFS will require further studies including a larger number of patients.…”
Section: Discussionsupporting
confidence: 85%
“…Borderline hypothalamic -pituitary dysfunction may be an etiology for EFS after GnRH agonist trigger. 11,14 Management of patients with EFS is a challenge for clinicians. Unfortunately no single treatment is known to be universally effective.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one study which reported prevalence of EFS comparing HCG versus GnRH agonist as trigger. 11 Ovulation was triggered with inj Triptorelin 200 mcg in view of high E2 level (risk for severe ovarian hyper stimulation syndrome) when 3 follicles had a size of > 18 mm diameter. Oocyte retrieval was done after 35 hrs of GnRH agonist trigger.…”
Section: Introductionmentioning
confidence: 99%
“…final oosit maturasyonu için GnRH agonisti uygulanan 2034 oosit donasyon siklusu ile hCG uygulanan 1433 ICSI siklusunu boş folikül sendromu açısından kıyasladıkları çalışmalarında sırasıyla %3.5 ve %3.1 şeklinde benzer oranlar tespit etmişlerdir. [20] Baum ve ark. yaptıkları geriye dönük analizde, tekrarlayan boş folikül sendromu için yüksek FSH düzeyi, ileri kadın yaşı, hCG günü estradiol seviye düşüklüğü ve uzun infertilite süresini risk faktörü olarak bildirmiş ve tekrarlama oranını %15.8 olarak rapor etmişlerdir.…”
Section: Discussionunclassified